2017
DOI: 10.1177/2041731417726428
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-responsive cell culture carrier: Effects on macrophage functionality and detachment efficiency

Abstract: Harvesting cultivated macrophages for tissue engineering purposes by enzymatic digestion of cell adhesion molecules can potentially result in unintended activation, altered function, or behavior of these cells. Thermo-responsive polymer is a promising tool that allows for gentle macrophage detachment without artificial activation prior to subculture within engineered tissue constructs. We therefore characterized different species of thermo-responsive polymers for their suitability as cell substrate and to medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…natants from RAW 264.7 murine macrophages with EBFCs were analyzed by a magnetic Luminex screening assay kit (R&D Systems, Minneapolis, MN, USA) according to the manufacturer's protocol 30,39 . The details of the protocols are provided in the supplementary data.…”
Section: Multiplex Screening Assay For Inflammatory Cytokine Releasementioning
confidence: 99%
See 1 more Smart Citation
“…natants from RAW 264.7 murine macrophages with EBFCs were analyzed by a magnetic Luminex screening assay kit (R&D Systems, Minneapolis, MN, USA) according to the manufacturer's protocol 30,39 . The details of the protocols are provided in the supplementary data.…”
Section: Multiplex Screening Assay For Inflammatory Cytokine Releasementioning
confidence: 99%
“…Herein, we employed two-dimensionally screen-printed carbon electrodes to prepare GDH-and GOD-based EBFCs, which included osmium redox polymer complexes as a mediator and BOD as a cathode. After the electrochemical characterization of the EBFC systems, the GDH-based EBFCs were applied to two different cells, human dermal fibroblasts as a major resident cell type for tissue organization and Raw 264.7 cells for the inflammatory response [28][29][30] , to investigate the cytotoxicity, cell migration effects, and cellular inflammatory response of the byproducts and electrical cues ( Fig. S1).…”
mentioning
confidence: 99%
“…Regarding avoidance of stress by Accutase and centrifugation, Rennert et al [ 31 ] also came to this conclusion, when investigating the influence of different thermoresponsive culture surfaces on macrophages [ 31 ]. Furthermore, studies on macrophages also indicated that enzymatic detachment techniques, although shown to be beneficial in terms of cell yield and viability, can induce profound phenotypic and functional changes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are no ethical issues associated with them, as hDPSCs are extracted from third molars, which are human-derived waste. However, investigations of the biological effects against other types of cells in pulp tissue, such as macrophages, neurons, and fibroblasts, are necessary to enhance our knowledge regarding possible adverse effects on pulp tissue from bulk-fill resins in deep cavities [44].…”
Section: Discussionmentioning
confidence: 99%